Computational investigation of the haemodynamics shows criticalities of central venous lines used for chronic haemodialysis in children - Bruno, Claudia; Sauvage, Emilie; Simcock, Ian; Redaelli, Alberto; Schievano, Silvia; Shroff, Rukshana; Capelli, Claudio (Frontiers in Pediatrics, 2022)
Background: Haemodialysis is a life-saving treatment for children with kidney failure. The majority of children have haemodialysis through central venous lines (CVLs). The use of CVLs in pediatric patients is often associated to complications which can lead to their replacement. The aim of this study is to investigate haemodynamics of pediatric CVLs to highlight the criticalities of different line designs. Methods: Four models of CVLs for pediatric use were included in this study. The selected devices varied in terms of design and sizes (from 6.5Fr to 14 Fr) . Accurate 3D models of CVLs were reconstructed from high-resolution images including venous and arterial lumens, tips and side holes. Computational fluid dynamics (CFD) analyses were carried out to simulate pediatric working conditions of CVLs in ideal and anatomically relevant conditions. Results: The arterial lumens of all tested CVLs showed the most critical conditions with the majority of blood flowing through the side-holes. A zone of low flow was identified at the lines’ tip. The highest shear stresses distribution (>10Pa) was found in the 8Fr line while the highest platelet lysis index in the 10Fr model. The analysis on the anatomical geometry showed an increase in wall shear stress measured in the 10F model compared to the idealised configuration. Similarly, in anatomical models an increased disturbance and velocity of the flow was found inside the vein after line placement. Conclusion: This study provided a numerical characterization of fluid dynamics in pediatric CVLs highlighting performance criticalities (i.e. high shear stresses and areas of stagnation) associated to specific sizes (8Fr and 10Fr) and conditions (i.e. anatomical test).